Imunopatologi Sjogren Syndrome (SS) melalui Salivary Epithelial Cells (SGEC) - Nur Ariska Nugrahani (Muhammadiyah University Press, 2022)
Sjogren's Syndrome is the second most autoimmune disease with average indications including decreased secretory creation from the essential exocrine organs, lacrimal organs, and salivary organs. This review means to look into the component of the immunopathology of Sjogren's disorder through Salivary Gland Epithelial Cells. Sjogren's condition will at first trigger the creation of enormous quantities of resistant cells like CD4+ T cells, CD8+ cells, the number of B cells, macrophages, and dendritic cells that will invade target organs like the salivary and lacrimal organs. The cells of the inborn invulnerable framework related to Sjogren's disorder are dendritic cells, macrophages, and NK cells. Dendritic cells in patients with Sjogren's Syndrome play a part as antigen-introducing cells (APC) in atopic germinal focuses in the salivary organs. Macrophages will be enlisted into the salivary organ tissue towards lymphocytes, bringing about an increment in macrophages and making the salivary organs grow. Salivary organ epithelial cells (SGECs) created in the acini organs and epithelial cells will have a cell polarization measure that is constrained by cell-to-cell connections towards the extracellular grid (ECM) through tight-junction.Keywords: Immunopathology, Sjogren Syndrome, Salivary Gland